Students' Use of Vocabulary and Kanji in Essays: Corpus Data-Based Measurement - Ai Sumirah Setiawati; Dwi Puspitosari; Danny Buyung Yudha Prasetya; Yulia Agustina (IJLHE: International Journal of Language, Humanities, and Education, 2023)
This research was conducted to describe 1) the level of Vocabulary and Kanji that students tend to use in essays measured based on JLPT standards and 2) the suitability of the level of Vocabulary and Kanji used by students in Japanese essays with the learning level that has been taken, namely N4. These two measurements utilize a corpus of data that has only been used for reading-learning purposes. This research uses a qualitative approach, and the data source is 53 students with data collection techniques, namely assignments to write essays with predetermined themes and questionnaires. The data analyzed is the vocabulary and Kanji students use in their essays. This research shows that students use 68.8% of N5-level vocabulary and 61% of N5-level Kanji in their essays. The findings from assessing the use of vocabulary and Kanji differ from their current learning level, namely level N4, which the highest percentage at this level should indicate. Thus, the target of students' ability to use N4-level vocabulary and Kanji at their current learning level has not been achieved.